Education Based on Art as Inclusive Education - Anđela V. Đuković; Ivana D. Mrvoš; Ivica V. Radovanović (University of Belgrade, Teacher Education Faculty, 2020)
Inclusive education is among fundamental problems in education which has instigated a lot of research and theoretical debates and has become a significant aspect of the education system reforms aimed at radical changes that would result not only in placing the marginalized children in the center of attention, but also in equality and quality of education for all children through the creation of an open and flexible education system. The paper looks at the key characteristics underlying the concept of inclusive education on one hand, and constituting the basis for using art in education, on the other, with the ultimate goal of identifying the values on which the idea of art in education is based and pointing to the opportunities it offers for developing a good quality education for all children. Two critical aspects ‒ an increased academization of the curricula and marginalization of art, and the perception and assessment of individual differences ‒ have been analyzed in the paper. By elaborating on the importance of art in education in general, and especially in the education of children with developmental and learning difficulties, the authors of the paper stress the potential of art for changing perceptions and the culture of teaching, as well as educational institutions, by making them more flexible and open for diversity.